PENGARUH MENGHAFAL AL-QUR’AN TERHADAP KECERDASAN EMOSIONAL SANTRI KOMPLEK DARUL AMIN DI PP ROUDLOTUL QUR’AN TLOGOANYAR LAMONGAN - Rokim Rokim; Farhatun Ni’mah (Akademika, 2022)
This research was motivated by how to develop emotional intelligence to achieve success with EQ (Emotional Quotient) using Al-Qur'an memorization as a method. The formulation of the problem is 1) How to memorize al-Qur'an for students of the Darul Amin complex in PP Roudlotul Qur'an. 2) How is the emotional intelligence of the students of the Darul Amin complex in PP Roudlotul Qur'an. 3) Ho the effect of memorizing al-Qur'an on the emotional intelligence of the Darul Amin complex students in PP Roudlotul Qur'an. This research uses quantitative methods and the type of research was descriptive quantitative. As for the results of the research are as follows: 1) Memorizing al-Qur'an students of the Darul Amin complex in PP Roudlotul Qur'an was considered good. With the percentage obtained results of 71.93%, this value was categorized with the score interpretation criteria and the between of interval value was 51%-75% which means it was included in good criteria. 2) The emotional intelligence students of Darul Amin complex in PP Roudlotul Qur'an was classified as good With the percentage obtained results of 74,57%, the value was categorized by the score interpretation criteria and the between of interval value was 51% -75% good criteria. 3) From the calculation results using a simple linear regression formula. There wasa significant effect of memorizing al-Qur'an on the emotional intelligence of students in the Darul Amin complex in PP Roudlotul Qur'an, obtaining the results of calculations with a very strong level of effectiveness.